Galician Oilfields - Morawski, Wojciech (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2017)
The article begins with the genesis of oil extraction and usage in Galicia, and concentrates on the interwar period. It shows the evolution of the usage of oil, from lighting towards combustion engines, and follows the structural problems this posed for the sector. It maps out extraction between particular oil fields, and explores how the profile of production changed over time. Finally, it deals with the role of foreign capital, the processes of monopolisation, and the impact of the sector on the local society.